Are microfinance institutions in South-East Asia pursuing objectives of greening the environment?. Issue 2 (3rd April 2018) - Mia, Md Aslam; Zhang, Miao; Zhang, Cheng; Kim, Yoomi
ABSTRACT: Microfinance institutions (MFIs) were initially established to alleviate extreme poverty by providing a wide array of customized financial products. However, today's MFIs' roles have been diversified into providing not only basic financial products but also a great variety of non-financial products, such as incentives and assistance to promote environment-friendly practices in the developing countries. By using an unbalanced panel data of 274 MFIs in South-East Asia from 2000 to 2014, this study investigated MFIs' contribution in greening the environment using the proxy of greenhouse gas (GHG) emissions from the agriculture sector. The regression results show that the main proxy variables: number of borrowers, number of loans outstanding and average loan over gross national income per capita have a negative effect on GHG emissions, and thus, creating a positive impact on greening our environment.